Programming Self-Efficacy in Higher Education Research: A Systematic Literature Review - Thiyaporn Kantathanawat; Siwalai Chinchua; Somkiat Tuntiwongwanich (Journal of Higher Education Theory and Practice, 2023)
The goal of the systematic literature review (SLR) was to provide an overview of the concepts and factors associated with programming self efficacy (PSE) from 2017 to 2021 in Scopus (215) and the Web of Science (310) academic indexes. From the initial 525 articles identified, 405 were left after duplication identification. Using further criteria such as article years must be between 2017 and 2021 in English, and through a peer-review process, 60 remained. These 60 papers were then analyzed using a set of questionnaires, from which 36 articles were excluded. Finally, 24 articles were selected for further analysis and to answer the study’s research questions. Results revealed that student success in information communication technology (ICT) and computer programming courses was from making the learners aware of their programming abilities. Therefore, higher education (HE) institutions should be encouraged to review learners’ abilities in programming and their related perceptions. Finally, institutions should create a relevant learning strategy using tools appropriate for improving education quality.
Keywords: Online Learning and Analytics; Technology-Enhanced Education Studies; E-Learning and COVID-19